2018
DOI: 10.1002/sctm.17-0157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Interaction of Cord Blood Hematopoietic Stem/Progenitor Cells with Functionally Integrated Three-Dimensional Microenvironments

Abstract: Despite advances in ex vivo expansion of cord blood‐derived hematopoietic stem/progenitor cells (CB‐HSPC), challenges still remain regarding the ability to obtain, from a single unit, sufficient numbers of cells to treat an adolescent or adult patient. We and others have shown that CB‐HSPC can be expanded ex vivo in two‐dimensional (2D) cultures, but the absolute percentage of the more primitive stem cells decreases with time. During development, the fetal liver is the main site of HSPC expansion. Therefore, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Taking advantage of extramedullary niches where HSC naturally go through an extensive expansion phase during development, the fetal liver has been hypothesized to be an exciting alternative to the model. Ferret-derived fetal livers were decellularized and repopulated with human fetal liver-derived stromal cells before infusing UCB HSC and HPC ( Mokhtari et al, 2018 ). This top-down approach harnessed in vivo produced ECM with native structure to better recreate the fetal liver niche.…”
Section: Ex Vivo Expansion Of Hsc and Hpcmentioning
confidence: 99%
“…Taking advantage of extramedullary niches where HSC naturally go through an extensive expansion phase during development, the fetal liver has been hypothesized to be an exciting alternative to the model. Ferret-derived fetal livers were decellularized and repopulated with human fetal liver-derived stromal cells before infusing UCB HSC and HPC ( Mokhtari et al, 2018 ). This top-down approach harnessed in vivo produced ECM with native structure to better recreate the fetal liver niche.…”
Section: Ex Vivo Expansion Of Hsc and Hpcmentioning
confidence: 99%
“…Demerdash et al (25) indicated that the number of expansion times of the feeder culture system were limited and that the growth ability of UCBSCs was reduced following differentiation for a certain number of generations. Furthermore, the authors of that study demonstrated that feeder layer cells weakened the effect of exogenous factors on UCBSCs and the animal/human-derived feeder layer was unable to achieve its clinical effect due to contamination with heterogenic/allogeneic antigens (23,(26)(27)(28)(29).…”
Section: Differentiation Of Ucbscsmentioning
confidence: 99%
“…However, current 2D in vitro culture and expansion strategies lead to a reduction in the absolute percentage of the most primitive stem cell number over time, so reducing the regenerative potential of CB. A new S tem C ells T ranslational M edicine study from the laboratories of Shay Soker and Graça Almeida‐Porada (Wake Forest Institute for Regenerative Medicine, North Carolina, USA) recently explored CB culture using conditions that mimic the 3D fetal liver niche of primitive HSPCs . To this end, Mokhtari et al developed a 3D scaffold constructed from extracellular matrix components seeded with liver or bone marrow cells and, encouragingly, the recreation of a 3D niche inhibited the decrease in the proportion of primitive HSPCs during culture and expansion, irrespective of the cell type used.…”
Section: Featured Articlesmentioning
confidence: 99%